Comparison of accusations against physicians and the practice of defensive medicine between surgical and non-surgical specialties - Ayat Mahmoud Tawfik; Safaa ElZoghby; Noura Mahmoud Elsherbiny; Marwa Rashad Salem (PLoS ONE, 2026)
Background Defensive medicine has two forms: positive (assurance behavior) or negative (avoidance behavior), depending on the clinical situation. Defensive medicine minimizes the risk of litigation and tends to vary between surgical and non-surgical specialties due to the nature of the risks involved and the potential for litigation. This study aimed to investigate the prevalence and patterns of defensive medicine practice among Egyptian physicians, compare surgical versus non-surgical specialties, and examine their correlation with medico-legal complaints and occupational determinants. Methods This cross-sectional study was conducted among physicians from surgical and non-surgical specialties working in different Egyptian hospitals. A self-administered online questionnaire was distributed using the snowball sampling technique. The Defensive Medicine Behavior Scale (DMBS) was used to assess the practice of defensive medicine. Results A sample of 210 physicians with a mean age of 39 ± 7 years was included; 51.4% held the highest qualification of M.D. or Ph.D., with an equal sex distribution (1:1). There was a high level of defensive medicine practice in both surgical and non-surgical specialties: 41.7% and 39.5%, respectively. However, the difference between the two groups was not statistically significant (P-value >0.05). Regression analysis showed that working at university hospitals and having workplace insurance coverage for medico-legal claims were associated with fewer positive defensive medicine practices. Conversely, concerns about the financial implications of medico-legal claims and negative reactions from patients or families were associated with a greater prevalence of positive defensive medicine practices. Conclusion Despite the high prevalence of defensive medicine practices, no statistically significant differences were observed between the surgical and non-surgical groups regarding overall engagement in defensive medicine.